Retention of the Hard-core Unemployed - Fottler, Myron D. (Academy of Management Journal, 1978)
Previous attempts to determine correlates of successful employer experience with the hard core unemployed have been restricted because of their focus upon a limited number of variable sets and lack of follow-up over time. The present study examines the impact of individual, organizational and program variables on the success of 104 manpower program participants over time. Results provide support for the systems approach to the design and evaluation of such programs as well as for expectancy theory in the explanation of results.